Increasing the Activeness and Learning Outcomes of Speech Writing Skills in Indonesian Language Subjects through the 3M strategy - Putri, Maria Theresia Dewi Anggraeni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of the study is to determine learning activities and learning achievements with the 3M learning model in an effort to improve the quality of education. Theoretical studies that support research are the concepts of learning, teaching, and learning, learning with the 3M learning model, and appropriate teaching materials. The method in action research is Classroom Action Research, which is a method carried out systematically by teachers or researchers with the aim of implementing educational innovations and improving the quality of learning outcomes. PTK is research that raises actual problems carried out by teachers which is an examination of learning activities which are actions to improve and improve learning practices in the classroom more professionally with research steps consisting of planning, implementation, observation and reflection. The results of action research obtained learning activeness showed memory of «»10%« with the achievement of KKM equal to or more than »75« increased by »59%«.